In situ deposition of 0D CeO2 quantum dots on Fe2O3-containing solid waste NH3-SCR catalyst: Enhancing redox and NH3 adsorption ability. (15th July 2022) - Chen, Yangfan; Zhang, Yuchen; Feng, Xin; Li, Jiangling; Liu, Weizao; Ren, Shan; Yang, Jian; Liu, Qingcai
Highlights: Fe2 O3 -containing solid waste was successfully utilized as NH3 -SCR catalyst. The deposition of CeQDs greatly enhanced redox and NH3 adsorption of catalyst. The optimal amount of CeQDs increased the NO conversion by more than 3.15 times. The N2 selectivity and SO2 tolerance of catalyst were enhanced by CeQDs depositing. DFT calculations describing the adsorption of O2 and NH3 were applied. Abstract: As NO x has been turning into a crucial environmental problem, NH3 -SCR technology with relatively simple device, reliable operation and low secondary pollution, has become a widely used commercial and mature de-nitration technology. However, some weaknesses restricted the further application of commercialized V2 O5 -WO3 /TiO2 NH3 -SCR catalysts, while Fe2 O3 -based catalysts have received much attention due to their high thermal stability, passable N2 selectivity and low cost. In this study, Fe2 O3 -containing solid waste derived from Zn extraction process of electric arc furnace dust was exploited as the base material for catalyst preparing. Owing to the complementary and synergistic effect of CeO2 and Fe2 O3, 0D CeO2 quantum dots (CeQDs) with fully-exposed active sites, large specific surface area, and rapid charge transfer have been introduced and deposited onto Fe2 O3 -containing solid waste nanorods. The in-situ deposition of CeQDs led to the admirable enhancement in NH3 -SCR catalytic activity, N2 selectivity and SO2 tolerance of the extremely low-cost Fe2 O3 catalyst. Comprehensive characterizations and DFT calculations describing the adsorption of O2 and NH3 were applied to analyze the catalyst structure and further investigate the detailed relationship between structural properties and activity as well as reaction mechanism. This work provides new insights for the high-value utilization of iron-containing solid waste and a practical reference for boosting the performance of NH3 -SCR catalysts by introducing quantum dots.